Thresholds for oximetry alarms and target range in the NICU: an observational assessment based on likely oxygen tension and maturity - Thomas E. Bachman; Narayan P. Iyer; Christopher J. L. Newth; Patrick A. Ross; Robinder G. Khemani (BMC, 2020)
Abstract Background Continuous monitoring of SpO2 in the neonatal ICU is the standard of care. Changes in SpO2 exposure have been shown to markedly impact outcome, but limiting extreme episodes is an arduous task. Much more complicated than setting alarm policy, it is fraught with balancing alarm fatigue and compliance. Information on optimum strategies is limited. Methods This is a retrospective observational study intended to describe the relative chance of normoxemia, and risks of hypoxemia and hyperoxemia at relevant SpO2 levels in the neonatal ICU. The data, paired SpO2-PaO2 and post-menstrual age, are from a single tertiary care unit. They reflect all infants receiving supplemental oxygen and mechanical ventilation during a 3-year period. The primary measures were the chance of normoxemia (PaO2 50-80 mmHg), risks of severe hypoxemia (PaO2 ≤ 40 mmHg), and of severe hyperoxemia (PaO2 ≥ 100 mmHg) at relevant SpO2 levels. Results Neonates were categorized by postmenstrual age: < 33 (n = 155), 33-36 (n = 192) and > 36 (n = 1031) weeks. From these infants, 26,162 SpO2-PaO2 pairs were evaluated. The post-menstrual weeks (median and IQR) of the three groups were: 26 (24-28) n = 2603; 34 (33-35) n = 2501; and 38 (37-39) n = 21,058. The chance of normoxemia (65, 95%-CI 64-67%) was similar across the SpO2 range of 88-95%, and independent of PMA. The increasing risk of severe hypoxemia became marked at a SpO2 of 85% (25, 95%-CI 21-29%), and was independent of PMA. The risk of severe hyperoxemia was dependent on PMA. For infants < 33 weeks it was marked at 98% SpO2 (25, 95%-CI 18-33%), for infants 33-36 weeks at 97% SpO2 (24, 95%-CI 14-25%) and for those > 36 weeks at 96% SpO2 (20, 95%-CI 17-22%). Conclusions The risk of hyperoxemia and hypoxemia increases exponentially as SpO2 moves towards extremes. Postmenstrual age influences the threshold at which the risk of hyperoxemia became pronounced, but not the thresholds of hypoxemia or normoxemia. The thresholds at which a marked change in the risk of hyperoxemia and hypoxemia occur can be used to guide the setting of alarm thresholds. Optimal management of neonatal oxygen saturation must take into account concerns of alarm fatigue, staffing levels, and FiO2 titration practices.